Enhancing Elementary Students' Science Learning Outcomes Through Inquiry-Based Learning Assisted by Concrete Media on Force Effects - Elsa Ramadani; Sarintan N Kaharu; Pahriadi Pahriadi; Zulnuraini Zulnuraini; Putriwanti Putriwanti (Papanda Publisher, 2026)
This study aims to determine the effect of the Inquiry learning model assisted by concrete media on student learning outcomes in the material of force effects on objects in grade IV SD Inpres Bumi Sagu. This study uses a quantitative method with a Quasi Experiment design using Nonequivalent Control Group Design. The research subjects involved class IV A as the control class (19 students) and class IV B as the experimental class (19 students). The instruments used included learning outcome tests in the form of 22 multiple-choice questions that had been tested for validity and reliability, as well as interview guidelines to explore students' learning experiences. Data were analyzed descriptively and inferentially using Independent Sample T-Test. The research results show that the average pretest score of the experimental class was 53.95, increasing to 90.37 on the posttest, while the control class increased from 63.21 to 81.74. The Independent Sample T-Test shows a significance value of 0.000 < 0.05, which means Ha is accepted and Ho is rejected. Interview results support the quantitative findings, showing that students in the experimental class experienced increased conceptual understanding, learning motivation, and critical thinking skills. Students in the low, medium, and high categories all felt the benefits of more meaningful learning through direct experience with concrete media. Thus, the Inquiry learning model assisted by concrete media is proven effective in improving student learning outcomes in science learning on the material of force effects on objects in grade IV SD Inpres Bumi Sagu.